Space Science Reviews - Bloemen, Hans.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Space Science Reviews (SSR) is an international journal on scientific space research. Its purpose is to provide a contemporary synthesis of the various branches of space research, with emphasis on scientific results and instruments in the fields of astrophysics, physics of planetary systems, solar physics, and physics of magnetospheres & interplanetary matter. SSR publishes invited papers and topical volumes. SSR does not publish original research papers.
Keywords: Planetology; Astrophysics; Space sciences; Aerospace engineering; Astronautics; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics) .; Planetology; Aerospace Technology and Astronautics; Astrophysics and Astroparticles